EFEKTIVITAS MUROTAL AL MULK TERHADAP NYERI PADA IBU POST PARTUM SECTIO CAESAREA - Siti Haniyah; Noor Yunida Triana; Indri Wijayanti (Universitas Pesantren Tinggi Darul Ulum, 2023)
Postpartum Sectio Caesare mothers feel discomfort in the form of pain due to the loss of the anesthetic effect. Previous studies have shown moderate pain at the highest score of 35 and the lowest score of 15% in the distribution of mild pain scales. Measures to deal with pain can be done with non- pharmacological measures, one of which is murottal therapy. The purpose of this study was to determine the effect of Al-Mulk murottal therapy on post partum pain of Sectio Caesaria at Siaga Medika Purbalingga General Hospital. This study used a quasi-pre-experimental method with a non-randomized study design using a control group and using a pre- and post-treatment test, namely a design involving two treatment groups and a comparison group. The population in this study were post partum SC mothers in the Mother and Child Room at Siaga Medika General Hospital, Purbalingga. Sampling was done by purposive sampling technique. The sample size to be used in this study was 56 respondents divided into 28 experimental groups and 28 control groups. There is an effect of Al Mulk murotal therapy on reducing pain before and after post partum Sectio Caesarea patients at Siaga Medika Purbalingga General Hospital in the control group with a p value of 0.025 (p <0.05) and experiments with a p value of 0.002 (p <0 , 05) Keywords: Murotal al Mulk, Post sectio caesarea pain, Postpartum